2020
DOI: 10.1126/sciadv.aay0589
|View full text |Cite
|
Sign up to set email alerts
|

Targeted anti–IL-1β platelet microparticles for cardiac detoxing and repair

Abstract: An acute myocardial infarction (AMI) induces a sterile inflammatory response that facilitates further heart injury and promotes adverse cardiac remodeling. Interleukin-1β (IL-1β) plays a central role in the sterile inflammatory response that results from AMI. Thus, IL-1β blockage is a promising strategy for treatment of AMI. However, conventional IL-1β blockers lack targeting specificity. This increases the risk of serious side effects. To address this problem herein, we fabricated platelet microparticles (PMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…In addition, bioengineering makes delivery of therapeutics more accessible, for instance, a damage-responsive delivery of paracrine products. Li et al [ 159 ] fabricated platelet microparticles (PMs) armed with anti–IL-1β antibodies, which take advantage of the spontaneous homing properties of platelets towards an injury site. After intravenous injection, the PMs precisely neutralized proinflammatory IL-1β in the injured heart and improved the outcomes of cardiac injury ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bioengineering makes delivery of therapeutics more accessible, for instance, a damage-responsive delivery of paracrine products. Li et al [ 159 ] fabricated platelet microparticles (PMs) armed with anti–IL-1β antibodies, which take advantage of the spontaneous homing properties of platelets towards an injury site. After intravenous injection, the PMs precisely neutralized proinflammatory IL-1β in the injured heart and improved the outcomes of cardiac injury ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…34 Li and colleagues produced microparticles with anti-IL-1β antibodies and they found that these microparticles neutralized IL-1β after MI, prevented cardiac remodeling, and induced cardiac repair. 8 In present study, we utilized the membrane from macrophages overexpressing the receptors of TNF-α, IL-1β, and IL-6 and coated to the NP miR199a-3p . We found that the macrophage membrane coated NP miR199a-3p (MMNP miR199a-3p ) can bind to and absorb TNF-α, IL-1β, and IL-6 while NP miR199a-3p cannot.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Blockage of TNF-α, IL-1, and IL-6 has been shown to preserve the cardiac function, indicating targeting these inflammatory cytokines should be a potential therapeutic approach to treat MI. [8][9][10][11] MicroRNAs (miRNAs) are short non-coding RNAs, which regulate gene expression. MiRNAs are shown to regulate various aspects of cardiomyocyte biology.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al 103 showed that active platelet-derived EVs delivering miRNA-339, miRNA-223, and miRNA-21 inhibit the expression of platelet-derived growth factor receptor-beta (PDGFRβ) in vascular smooth muscle cells (SMCs) and increase the number of capillaries in ischemic myocardium. Li and colleagues 104 indicated that anti-IL-1 platelet-derived EVs remove cytotoxic IL-1 and repair ischemic myocardium during AMI. Li et al suggested that coronary serum exosomes in patients with MI regulate angiogenesis through miR-939-mediated nitric oxide signaling pathway 105 .…”
Section: The Roles Of Extracellular Vesicles In Heart Diseasesmentioning
confidence: 99%